PENILAIAN KECURANGAN: PENGALAMAN, PELATIHAN DAN TINDAKAN SUPERVISI - Michael Prasetya D, Mulyani (Jurnal Akuntansi, 2018)
The auditor's inability to detect fraud, is not up to the expectations of financial statement users. Experiences, Training and Supervision Measures are the 3 most important essential components an auditor must have in a fraudulent area..The purpose of this research are to conduct research to prove whether experience, training and supervision actions affect the assessment of fraud.The survey method with questionary used in this reasarch. The object of this research are auditors who worked in one of the big four Accounting Firms in Jakarta. The sampling technique used is purposive sampling. The result of this research shows that the variable of experience, training and supervision actionhave positive influence to the variable of fraud detection. Keyword: Auditor Experience, Training , Supervision Action and Fraud Detection